PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. PELINDO (PERSERO) CABANG TERMINAL PETIKEMAS MAKASSAR - Fernia Eka Wardana Sasha Nabila; M. Ikhwan Maulana Haeruddin; Burhanuddin; Uhud Darmawan Natsir; Muh. Ichwan Musa (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of compensation on employee performance at PT. Pelindo (Persero) Cab. Makassar Container Terminal. The independent variable in this study is Compensation while the dependent variable is Employee Performance. The population in this study are employees who work at PT. Pelindo (Persero) Makassar Container Terminal Branch. While the sample used was 54 respondents. The sampling technique in this study was carried out using a simple random sampling method (Simple Random Sampling method). Data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression analysis using SPSS 25.00 for windows. The results showed that the compensation variable has a significant effect on the employee performance variable at PT. Pelindo (Persero) Makassar Container Terminal Branch. This is proven by obtaining the correlation value. Which means if the compensation is assumed to be zero or no compensation occurs, the performance of employees at PT. Pelindo (Persero) Makassar Container Terminal Branch has not changed, but if compensation has increased by one unit, then this can affect employee performance at PT. Pelindo (Persero) Makassar Container Terminal Branch.